Time to Reconsider the Role of Relative Blood Volume Monitoring for Fluid Management in Hemodialysis. Issue 6 (November 2018) - Keane, David F.; Baxter, Paul; Lindley, Elizabeth; Rhodes, Laura; Pavitt, Sue
Abstract : Relative blood volume (RBV) monitoring during hemodialysis has been used to help guide fluid management for decades, although with little supporting evidence. The technique relies on the assumption that variation in RBV during fluid removal reflects the capacity for vascular refilling and that efficient refilling is related to fluid overload. This study investigated the relationship between RBV variation and bioimpedance-based fluid overload in 47 patients on stable hemodialysis. Mean treatment ultrafiltration volume (UFV) was 1.7 L and RBV reduction was 3.2%/hour. Relative blood volume slopes were grouped based on trajectory: flatline (no decrease), linear decrease, or linear decrease followed by flatline. Fluid overload was similar ( p > 0.05) across groups pre-dialysis (1.0, 2.2, and 1.6 L, respectively) and post-dialysis (−0.8, −0.1, and −0.1 L), whereas UFV was higher in patients with a linear decrease (1.8, 2.5, and 1.6 L; p = 0.02). Specific ultrafiltration rate, but not fluid overload, was associated with RBV change over dialysis. At least half the patients in each group finished dialysis fluid depleted based on bioimpedance, suggesting that the link between refilling and fluid overload is not as straightforward as previously assumed. These results question the assumptions that the absence of an appreciable decrease in RBV indicates fluid overload, and a rapid fall suggests fluid depletion.